Determinants of effective succession in family businesses and their influence on decision making - Fahed-Sreih, Josiane (2016)
To discover new determinants of effective succession in family businesses and their influence on decision making, six Lebanese family businesses were interviewed using a qualitative approach. Those determinants include the heirs' outside work experience; the father as a good example for the heirs; being treated as a non-family member; the reliance on outsiders; the hard work imposed on the heirs and a rational thought system of the fathers. This study examined the influence of these determinants and the strategic planning and family relationships' aspects on decision making. It showed how they enhance this process within family firms. As this study filled certain gaps in the literature, it suggested new areas for future studies.